2016
DOI: 10.1097/igc.0000000000000709
|View full text |Cite
|
Sign up to set email alerts
|

Careful Dissection of the Distal Ureter Is Highly Important in Nerve-sparing Radical Pelvic Surgery: A 3D Reconstruction and Immunohistochemical Characterization of the Vesical Plexus

Abstract: The vesical plexus is located in both layers of the vesicouterine ligament and has a very close relationship with the distal ureter. Complete mobilization of the ureter in RHL might cause bladder dysfunction due to sympathetic and parasympathetic denervation. Hence, the distal ureter should be regarded as a risk zone in which the vesical plexus can be damaged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Despite the introduction of several anastomotic techniques, none of them ensure long‐lasting results (Wiesner & Thüroff, ). The extensive scarring is related to microtraumatisation of the urethral and ureteric vascular plexus that is difficult to omit or even recognise during surgery (Kraima et al, ). Subsequently, developing anoxia due to insufficient blood supply is responsible for surgical urethra (20%) and ureter (40%) repair failures.…”
Section: Current Limitations Of Reconstructive Urologymentioning
confidence: 99%
“…Despite the introduction of several anastomotic techniques, none of them ensure long‐lasting results (Wiesner & Thüroff, ). The extensive scarring is related to microtraumatisation of the urethral and ureteric vascular plexus that is difficult to omit or even recognise during surgery (Kraima et al, ). Subsequently, developing anoxia due to insufficient blood supply is responsible for surgical urethra (20%) and ureter (40%) repair failures.…”
Section: Current Limitations Of Reconstructive Urologymentioning
confidence: 99%
“…Numerous reports have discussed the details about the anatomy and neurological function of IHP 1518 , but only several studies have been conducted on the IHC analysis of pelvic nerves 1924 . There were fewer reports about the IHC method for IHP recognition 1921 , and almost none compared the areas, proportion or impairment of nerve fibers as we did. A study on 15 donated female cadavers revealed that the cardinal ligament did not contain the PSNs, and a well-defined fascial structure existed in the bottom or dorsal margin of the cardinal ligament area.…”
Section: Discussionmentioning
confidence: 74%
“…Kraima et al . (18) reported that the bladder branches of the IHP have a more diffuse pattern of distribution in the posterior vesico-uterine ligament, often intimately associated with multiple veins. Therefore, it is often difficult to clearly identify and completely preserve all the bladder branches, and we can only rely on the middle or inferior vesical veins as landmarks for approximate locations of the bladder branches.…”
Section: Discussionmentioning
confidence: 99%
“…Kraima et al . (18) performed an anatomical 3D reconstruction of the IHP bladder branches, showing divergent nerve fibers surrounding the distal ureter within the nerve plane dorsal to the ureter. Therefore, preservation of the dorsal nerve plane can preserve the bladder branches of IHP in a more integral fashion.…”
Section: Discussionmentioning
confidence: 99%